Credentialed Evaluator Designation Program, the Canadian Experience. Issue 145 (March 2015) - Kuji‐Shikatani, Keiko
Abstract: The Credentialed Evaluator (CE) designation is a service provided by Canadian Evaluation Society (CES) to its members, who may elect to become credentialed on a voluntary basis. The designation means that the holder has provided evidence of the education and experience required by the CES to be a competent evaluator. The author briefly examines the impetus for the CE designation, the value it represents for the Canadian evaluation community, the development of the system including structure and administration, and how it is evolving as we learn from professionalizing evaluation in Canada. Concerns expressed during the development of the Competencies for Canadian Evaluation Practice mirrored those expressed about the development of a professional designation. The CE designation is about providing a path for new evaluators and a clearer direction for more established evaluators for their ongoing development. © Wiley Periodicals, Inc., and the American Evaluation Association.